405 A NATURAL HISTORY OF VERY LONG-TERM BIORESORBABLE ATHEROSCLEROTIC RESTORATION THERAPY. (15th December 2022) - Fezzi, Simone; Rubino, Francesca; Del Sole, Paolo Alberto; Pesarini, Gabriele; Mammone, Concetta; Scarsini, Roberto; Lunardi, Mattia; Pighi, Michele; Tavella, Domenico; Ribichini, Flavio Luciano
Abstract: A 49-year-old man was referred to our cath-lab in 2015 after the detection of inducible ischaemia in the infero-lateral wall on single-photon emission CT performed due to a worsening stable angina. His cardiovascular risk factors accounted for family history of ischemic disease, high blood pressure and dyslipidaemia. The echocardiography highlighted a mildly reduced left ventricular function with infero-lateral wall hypokinesia. Coronary angiography revealed a chronic total occlusion (CTO) of the left circumflex artery (LCX) and a long diffuse severe disease of the right coronary artery (RCA). The left anterior descending artery (LAD) showed a diffuse atherosclerotic involvement without critical stenoses. Percutaneous coronary intervention (PCI) was performed after Heart Team discussion with implantation of two 3.5×28mm and 3.5×23mm Absorb bioresorbable vascular scaffold (BVS) on the RCA. Moreover, the LCX CTO was successfully treated by anterograde approach with implantation of a 3.0×28 mm Absorb BVS. Intravascular ultrasound confirmed the optimal result of both the interventions, while confirmed the long diffuse calcific involvement of the LAD with a thick cap calcific fibroatheroma at the virtual histology. The patient was discharged on dual antiplatelet therapy for twelve months. After five uneventful years, he was readmitted to our department for recurrence of worsening stable angina. At the coronary angiography a significant progression of the proximal LAD disease was noted. The lesion was judged hemodynamic relevant with pressure derived indices (instantaneous wave-free ratio 0.86; fractional flow reserve 0.70). The IVUS and optical coherence tomography (OCT) analysis confirmed the significant progression of the disease with a long, diffuse, sub-occlusive thick cap fibroatheroma stenosis (minimal lumen area 1.9 mm2; plaque burden 91%). The OCT analysis showed the complete resorption of the devices previously implanted to the RCA and the LCX, with optimal long-term results and positive remodelling in the LCX. Therefore, an OCT-guided PCI with marker-to-marker implantation of two 3.5×25 and 3×20 mm magnesium-based Magmaris BVS was performed. In 2022, the patient underwent an elective coronary angiography that demonstrated a complete resorption of both the Magmaris with an optimal OCT result. Conversely, the positive remodelled segment resulting from complete resorption of the poly-L-lactic-based BVS in the mid-LCX was shown to be progressed to a critical sub-occlusive fibroatheroma. A further OCT-guided PCI with deployment one 3.5×20mm Magmaris BVS was performed. Six months later, patient was asymptomatic with a good performance status. To the best of our knowledge, the present is the first case of multivessel repetitive imaging-based percutaneous revascularizations with the use of two different BVS technologies and a total of six devices implanted, with very long-term intracoronary imaging result. Through the paired intravascular imaging analysis, this case sought to provide insightful findings on vulnerable plaque atherosclerotic progression and on BVS biologic restoration therapy, a process that appears particularly appealing in young patients with advanced CAD, namely multivessel involvement and diffuse disease that still poses limitations to PCI.